Cutibacterium acnes Septic Arthritis of the Nonoperated Knee: A Case Report - Kelechi R. Okoroha (The Surgery Journal, 2017)
Cutibacterium (Propionibacterium) acnes, a gram-positive bacillus with low pathogenicity, is an uncommon but known cause of prosthetic joint infections, particularly related to shoulder surgery. C. acnes, however, is an extremely rare pathogen in the nonoperated knee joint. This report details an uncommon case of C. acnes septic knee arthritis after multiple intra-articular steroid injections in a 56-year-old male patient. After an indolent presentation and late diagnosis, the patient underwent surgical debridement with IV antibiotic management. This case illustrates that intra-articular corticosteroid injections for the management of osteoarthritis are not without risk. Literature supporting their use remains limited and clinicians should use proficient clinical judgment for appropriate patient selection for these injections. Vigilance following injections or aspirations of the knee should be maintained to identify the indolent clinical presentation of C. acnes septic arthritis.